Pengaruh Kepuasan Kerja Terhadap Turnover Intention Dengan Komitmen Organisasi Sebagai Variabel Intervening Pada Perusahaan Manufaktur Di Indonesia - Suwondo Suwondo; Tan Evan Tandiyono (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Human resources determine success in achieving the goals of a company. Companies must be able to manage and manage human resources, it requires a proper understanding of human resource management. Appropriate management of human resource management through employee job satisfaction, employee performance satisfaction is a positive attitude about the work produced, financial satisfaction, and good relations between fellow employees and superiors. If employee satisfaction is high, it will result in a decreased turnover ratio and vice versa, if employee satisfaction is low, it will be followed by an increase in the turnover ratio. Turnover intention is the tendency of employees’ intention to quit their jobs voluntarily. This makes the condition of the company unstable. The factors that influence turnover intention are job satisfaction and organizational commitment. The phenomenon that occurs is that many employees leave the company because employees are not willing to spend extra work time because the salary given is not appropriate, and co-workers are not supportive. Therefore, a study was conducted with the variables of job satisfaction and organizational commitment which are considered to influence turnover intention, with the object of research being PT LongHwa Jaya Timber Lamongan, which is a manufacturing company in the field of wood management. The purpose of this study was to analyze the effect of job satisfaction on turnover intention, analyze the effect of job satisfaction on organizational commitment, analyze the effect of job satisfaction on turnover intention and analyze the effect of job satisfaction on turnover intention with organizational commitment as an intervening variable. Using a quantitative approach with primary data sources, the population in this study were all employees of PT LongHwa Jaya Timber Lamongan with the results of the research that job satisfaction has a significant effect on organizational commitment to employees, and organizational commitment has a significant effect on turnover intention on employees and PT LongHwa Jaya Timber, Lamongan Regency.